Contrast-Enhanced Microtomographic Characterisation of Vessels in Native Bone and Engineered Vascularised Grafts Using Ink-Gelatin Perfusion and Phosphotungstic Acid. (23rd April 2017) - Sutter, Sarah; Todorov, Atanas; Ismail, Tarek; Haumer, Alexander; Fulco, Ilario; Schulz, Georg; Scherberich, Arnaud; Kaempfen, Alexandre; Martin, Ivan; Schaefer, Dirk J.
Abstract : Objectives . Bone ischemia and necrosis are challenging to treat, requiring investigation of native and engineered bone revascularisation processes through advanced imaging techniques. This study demonstrates an experimental two-step method for precise bone and vessel analysis in native bones or vascularised bone grafts using X-ray microtomography ( μ CT), without interfering with further histological processing. Methods . Distally ligated epigastric arteries or veins of 6 nude rats were inserted in central channels of porous hydroxyapatite cylinders and these pedicled grafts were implanted subcutaneously. One week later, the rats were perfused with ink-gelatin and euthanised and the femurs, tibias, and grafts were explanted. Samples were scanned using μ CT, decalcified, incubated with phosphotungstic acid (PTA) for contrast enhancement, rescanned, and processed histologically. Results. Contrast-enhanced μ CT displayed the course and branching of native bone vessels. Histologically, both central (−17%) and epiphyseal vessels (−58%) appeared smaller than in μ CT scans. Hydroxyapatite cylinders were thoroughly vascularised but did not display bone formation. Grafts with a central artery had more (+58%) and smaller (−52%) vessel branches compared to grafts with a vein. Conclusions . We present a relatively inexpensive and easy-to-perform two-step method to analyse bone and vessels by μ CT, suitable to assess a variety of bone-regenerative strategies.